Serum heat-shock protein-65 antibody levels are elevated but not associated with disease activity in patients with rheumatoid arthritis and ankylosing spondylitis - Ulusoy, Hasan; Akgol, Gurkan; Gulkesen, Arif; Kaya, Arzu; Kal, Gul Ayden; Kaman, Dilara; Tuncer, Turkan (Dove Medical Press Ltd, 2018)
Objectives: Heat-shock proteins (HSPs) have gained increased interest for their role in autoimmune disorders. These proteins are targeted by the immune system in various autoimmune diseases. The aim of this study was to assess the serum heat-shock protein-65 antibody (anti-HSP65) levels and their clinical significance in patients with rheumatoid arthritis (RA) and ankylosing spondylitis (AS). Patients and methods: A total of 30 patients with RA, 30 patients with AS, and 30 healthy controls were enrolled in this study. All patients were assessed using routine clinical and laboratory evaluations. Serum anti-HSP65 levels were determined by ELISA. Results: Serum anti-HSP65 levels of both RA and AS patients were significantly higher than those of controls (p= 0.014 and p= 0.001, respectively). No association was found between serum anti-HSP65 levels and disease activity in either RA or AS patients. There was a significant correlation between anti-HSP65 and anti-cyclic citrullinated peptide levels in patients with RA (p= 0.024). Conclusion: In this study, serum anti-HSP65 levels were increased, but not associated with disease activity in both RA and AS patients. These results suggest that HSP antigens may play a role in the pathogenesis. However, further follow-up studies are needed. Identification of target antigens such as HSP65 is vital to developing new immunotherapeutic agents.
Keywords: heat-shock protein; HSP; rheumatoid arthritis; ankylosing spondylitis